Together with Farmers, Exploring Adaptive and Economically Valued VegetationPost-Eruption of Mount Semeru: Bersama Petani Menggali Vegetasi Adaptif dan Bernilai Ekonomi Pasca ErupsiGunungSemeru - Kurniawan Sigit Wicaksono; Sri Rahayu Utami; Zaenal Kusuma; Mochtar Lutfi Rayes; Ustiatik, Reni; Istika Nita (Universitas Lancang Kuning, 2023)
Mount Semeru eruption in 2020 and 2021 damaged 851 ha of productive land. Restoration of the affected lands requires information such as wide area, distribution, and eruption material characteristics. This community service aimed to provide a database as an overview of pyroclastic materials characteristics and elucidate potential-and-adaptive plants and microbes on post-Mt. Semeru eruptions. The volcanic ash contains significant elements (Al, Si, K, Ca, Ti, and Fe) and minor elements (V, Cr, Mn, Cu, Zn, Sr, Ba, Eu, and Re). Some of the plants that have survived post-eruption are annual shrubs and herbaceous plants such as grasses, so these plants can be used to restore the affected lands fertility after the Mt Semeru eruption. Based on economic evaluation and conditions in the field, the recommended adaptive plants are Pennisetum puparium and Musa paradisiaca. Both plants provide economic benefits for animal feed and farmers' income during post-eruption land recovery.